2015
DOI: 10.1371/journal.pone.0133218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate and Rodent Factors on Hemorrhagic Fever with Renal Syndrome in Chongqing, China, 1997–2008

Abstract: China has the highest global incidence of hemorrhagic fever with renal syndrome (HFRS), constituting 90% of the cases in the world. Chongqing, located in the Three Gorges Reservoir Region, has been experiencing differences in the occurrence of HFRS from 1997 to 2008. The current study was designed to explore the effects of climate and rodent factors on the transmission of HFRS in Chongqing. Data on monthly HFRS cases, rodent strains, and climatic factors were collected from 1997 to 2008. Spatio-temporal analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
1
20
1
Order By: Relevance
“…These findings further supported our results. But, our finding is inconsistent with prior findings from studies to explore the relationship between other contagious diseases, such as scarlet fever (in Hong Kong) 65 , human brucellosis (in Hubei province) 22 , and HFRS (in Guangzhou and in Chongqing) 20,72 , and climatic factors. This discrepancy may mainly be owing to the various climatic characteristics of the study regions, along with different methods used to investigate the relevance in the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings further supported our results. But, our finding is inconsistent with prior findings from studies to explore the relationship between other contagious diseases, such as scarlet fever (in Hong Kong) 65 , human brucellosis (in Hubei province) 22 , and HFRS (in Guangzhou and in Chongqing) 20,72 , and climatic factors. This discrepancy may mainly be owing to the various climatic characteristics of the study regions, along with different methods used to investigate the relevance in the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, correlation analysis and multiple linear analysis were used to further explore the relationship between environmental factors and HFRS incidence in Anqiu City. Our results showed that there was a negative association between temperature and HFRS incidence in Anqiu City, which was supported by other previous studies [ 24,25]. High temperatures may limit the time available to farmers for outdoor activity and work, thereby reducing the opportunity for contact between people and field mice, which is one of the most common agricultural pests and a natural vector of hantavirus.…”
Section: Discussionsupporting
confidence: 90%
“…High temperatures may limit the time available to farmers for outdoor activity and work, thereby reducing the opportunity for contact between people and field mice, which is one of the most common agricultural pests and a natural vector of hantavirus. In addition, some studies have suggested that the breeding rate of rodents is highest at temperatures of 10-25°C, which are favourable conditions for outdoor activity and work [ 25]. Anqiu City is located in a warm temperate continental monsoon climate zone, and the annual average temperature is 12.2°C.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that hantavirus can be infected by inhaling the aerosol and ingesting the food contaminated by the rodent excreta, that is, the virus may transmit through respiratory and digestive tracts [5,8,[10][11][12]. The reason why cleaning spare rooms was the influencing factor might be that the human activities in the All exposure factors were within the previous 1 month prior to disease onset OR Odds ratio, CI Confidence interval spare rooms were infrequent and these rooms were poorly ventilated, which was conducive to rodent reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of hantaviruses is thought to occur mainly through contact with infected animal excreta or ingest food contaminated with infected animal excreta (faeces, urine and saliva). Though the aerosol route of infection is undoubtedly the most common means of transmission among rodents and to humans [5,8,[10][11][12], virus transmission by bite occurs among rodents and may also result in human infection [8].…”
Section: Introductionmentioning
confidence: 99%